The complete cat breed book - Dennis-Bryan, Kim (DK Pub., 2013)
Profiles one hundred cat breeds, with photographs for easy identification, information and advice for choosing the right breed, and details such as size, grooming, and sociability. Includes guidance on care, behavior, and common problems.